Investigating endocrine‐disrupting properties of chemicals in fish and amphibians: Opportunities to apply the 3Rs. (18th August 2021) - Burden, Natalie; Embry, Michelle R.; Hutchinson, Thomas H.; Lynn, Scott G.; Maynard, Samuel K.; Mitchell, Constance A.; Pellizzato, Francesca; Sewell, Fiona; Thorpe, Karen L.; Weltje, Lennart; Wheeler, James R.
Abstract: Many regulations are beginning to explicitly require investigation of a chemical's endocrine‐disrupting properties as a part of the safety assessment process for substances already on or about to be placed on the market. Different jurisdictions are applying distinct approaches. However, all share a common theme requiring testing for endocrine activity and adverse effects, typically involving in vitro and in vivo assays on selected endocrine pathways. For ecotoxicological evaluation, in vivo assays can be performed across various animal species, including mammals, amphibians, and fish. Results indicating activity (i.e., that a test substance may interact with the endocrine system) from in vivo screens usually trigger further higher‐tier in vivo assays. Higher‐tier assays provide data on adverse effects on relevant endpoints over more extensive parts of the organism's life cycle. Both in vivo screening and higher‐tier assays are animal‐ and resource‐intensive and can be technically challenging to conduct. Testing large numbers of chemicals will inevitably result in the use of large numbers of animals, contradicting stipulations set out within many regulatory frameworks that animal studies be conducted as a last resort. Improved strategies are urgently required. In February 2020, the UK's National Centre for the 3Rs and the Health and Environmental Sciences Institute hosted a workshop ("Investigating Endocrine Disrupting Properties in Fish and Amphibians: Opportunities to Apply the 3Rs"). Over 50 delegates attended from North America and Europe, across academia, laboratories, and consultancies, regulatory agencies, and industry. Challenges and opportunities in applying refinement and reduction approaches within the current animal test guidelines were discussed, and utilization of replacement and/or new approach methodologies, including in silico, in vitro, and embryo models, was explored. Efforts and activities needed to enable application of 3Rs approaches in practice were also identified. This article provides an overview of the workshop discussions and sets priority areas for follow‐up. Integr Environ Assess Manag 2022;18:442–458. © 2021 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). KEY POINTS: In vivo screening and higher‐tier assays to evaluate a chemical's potential endocrine‐disrupting properties and potential impacts on ecosystems are animal‐ and resource‐intensive and can be technically challenging to conduct. There has been much recent work to develop new approach methodologies (NAMs)—in silico and in vitro approaches—that can be applied in this space. An understanding of the opportunities and challenges with the current in vivo approaches, coupled with the ongoing efforts to expand the development, use, and application of NAMs, will help focus short‐ and long‐term goals. International, multisector science‐based activities provide the framework to improve ecological safety as it relates to compounds with endocrine‐disrupting properties.